Cure‐on‐demand wood adhesive based on the frontal polymerization of acrylates. Issue 40 (4th July 2016) - Holt, TreyVon; Fazende, Kylee; Jee, Elizabeth; Wu, Qinglin; Pojman, John A.
ABSTRACT: We demonstrated for the first time a cure‐on‐demand wood adhesive using thermal frontal polymerization with Southern Pine wood. Monomer structure, initiator loading, and filler loading all had an impact on the strength of the adhesive and the cure‐on‐demand ability. More flexible, ethoxylated monomers produced stronger adhesives; though, the ethoxylate groups reduce the ability of the system to be polymerized frontally. Addition of a highly reactive comonomer (acrylic acid) to increase molecular weight between crosslinks along with the ethoxylated triacrylate increased the propensity for frontal polymerization and made a tougher polymer. Increasing initiator loading could help ensure front propagation, but a maximum initiator loading was reached where the gaseous byproducts of the peroxide initiator made the network highly porous and thus lacking strength. Fillers such as kaolin and sawdust helped overcome decreases in strength at high initiator loadings. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44064. Abstract :